2017
DOI: 10.1007/s13224-017-0990-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy of Bupivacaine with Dexmedetomidine Versus Bupivacaine Alone for Transversus Abdominis Plane Block for Post-operative Analgesia in Patients Undergoing Elective Caesarean Section

Abstract: The addition of dexmedetomidine to bupivacaine in TAP block prolonged the duration of time at which first dose of rescue analgesia was sought and also reduced the total dose of opioid requirement in the first 24-h post-Caesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…In the current study, the results indicated that when compared with 0.3% ropivacaine alone, adding 0.5 µg/kg dexmedetomidine to 0.3% ropivacaine in TAP block prolonged pain-free duration, decreased post-operation VAS pain scores at 6 and 8 h post-surgery, reduced the number of patients who required rescue analgesic, prolonged the time to first request for analgesic and improved patient satisfaction without serious side effects. These results were consistent with a previous study by Ramya et al (31), which concluded that the addition of dexmedetomidine to bupivacaine in TAP block prolonged the time to first request of rescue analgesia and reduced the total dose of opioid requirement in the first 24 h post-CS. However, Ding et al (32) reported that adding dexmedetomidine did not significantly improve the quality or duration of TAP block.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the results indicated that when compared with 0.3% ropivacaine alone, adding 0.5 µg/kg dexmedetomidine to 0.3% ropivacaine in TAP block prolonged pain-free duration, decreased post-operation VAS pain scores at 6 and 8 h post-surgery, reduced the number of patients who required rescue analgesic, prolonged the time to first request for analgesic and improved patient satisfaction without serious side effects. These results were consistent with a previous study by Ramya et al (31), which concluded that the addition of dexmedetomidine to bupivacaine in TAP block prolonged the time to first request of rescue analgesia and reduced the total dose of opioid requirement in the first 24 h post-CS. However, Ding et al (32) reported that adding dexmedetomidine did not significantly improve the quality or duration of TAP block.…”
Section: Discussionsupporting
confidence: 93%
“…[ 33 ] Other studies also confirmed the previous finding in different abdominal operations. [ 34 35 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the use of whether topically or intravenously dexmedetomidine provided a deeper postoperatively analgesia and lesser extra analgesic consumption. In a study by Ramya et al ( 17 ) in two groups of 35 patients, TAP block was performed after cesarean section by spinal anesthesia. In group B, 20 ml of 0.25% bupivacaine was used, and in group BD, 20 mL of bupivacaine 0.25% and 0.5 µ/kg dexmedetomidine was used, and patients were given paracetamol (1 g) immediately after block and every 8 hours in the ward.…”
Section: Discussionmentioning
confidence: 99%
“…The drowsiness of patients after waking up have also been attributed to general anesthesia. Ramya et al ( 17 ) used spinal anesthesia and did not indicate that patients fell asleep. In the present study, due to the fact that TAP block was performed by spinal anesthesia at the end of surgery and no sedative drug was prescribed during the operation, patients clearly experienced sedation and drowsiness, which were seen in group L for up to 2 hours and in groups M and H up to 4 hours, and in some cases, drowsiness, especially in group H, caused latency in patients’ discharge from the recovery ward.…”
Section: Discussionmentioning
confidence: 99%